ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERATAAN LABA (INCOME SMOOTHING) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (2011-2015) - Anisa Dwi Wandani; Nur Hidayati; Muhammad Cholid Mawardi (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
AbstractThis study aimed to analyze factor-factor that affects alignment profit(income smoothing) in manufacturing companies who registered at theIndonesian stock exchange. Factor-factor income smoothing in this study the sizeof the company, Profitability (Return On Assets) and Financial Leverage.The population in this research is manufacturing companies listed inIndonesia Stock Exchange. The sampling technique used purposive sampling.Year study period from 2011 to 2015.The data were analyzed using multiple linear regression. The results ofthis study show that:1)The Size of the company has no effect in income smoothing.2)Return On Assets has no effect in income smoothing 3) Financial Leverage havean effect in income smoothing.Keywords: income smoothing, the size of the company, return on assets andfinancial leverage